2020
DOI: 10.1051/0004-6361/201937292
|View full text |Cite
|
Sign up to set email alerts
|

The WISSH quasars project

Abstract: Hyper-luminous quasars (Lbol ≳ 1047 erg s−1) are ideal laboratories to study the interaction and impact of the extreme radiative field and the most powerful winds in the active galactic nuclei (AGN) nuclear regions. They typically exhibit low coronal X-ray luminosity (LX) compared to the ultraviolet (UV) and mid-infrared (MIR) radiative outputs (LUV and LUV); a non-negligible fraction of them report even ∼1 dex weaker LX compared to the prediction of the well established LX–LUV and LX–LUV relations followed by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 64 publications
8
33
1
Order By: Relevance
“…To cover a wider range in luminosity, we added the AGN sample observed in the KASHz survey matched in redshift (z ∼ 2-2.5) and the high luminosity targets from the WISSH survey (e.g. Bischetti et al 2017;Martocchia et al 2017;Zappacosta et al 2020). We derived the Pearson coefficient and the p-value for each of these relations and the results are reported in Table 5.…”
Section: Scaling Relationsmentioning
confidence: 99%
“…To cover a wider range in luminosity, we added the AGN sample observed in the KASHz survey matched in redshift (z ∼ 2-2.5) and the high luminosity targets from the WISSH survey (e.g. Bischetti et al 2017;Martocchia et al 2017;Zappacosta et al 2020). We derived the Pearson coefficient and the p-value for each of these relations and the results are reported in Table 5.…”
Section: Scaling Relationsmentioning
confidence: 99%
“…12 that the properties of the CIV line correlate with all three of these parameters, but the highest significant correlation is with α OX . Recently, Zappacosta et al (2020), studying the WISSH sources, reported a significant correlation between the luminosity in the 2-10 keV band (L 2−10 keV ) and the blueshift of the CIV line, that is, objects exhibiting a high-velocity shift have lower L 2−10 keV . With the SUPER sample we are not able to properly investigate this relation.…”
Section: Connection Between CIV Velocity Shift and Agn Propertiesmentioning
confidence: 99%
“…(4) and (8). For the α OX we used the values reported inMartocchia et al (2017) andZappacosta et al (2020).…”
mentioning
confidence: 99%
“…5.8 ± 0.7%. The α ox − log λ Edd distribution of our fourteen high-λ Edd AGN, the XMM-COSMOS type-1 AGN of Lusso et al (2010), the suband super-Eddington AGN of Liu et al (2021) and the thirteen hyper-luminous WISSH QSOs of Zappacosta et al (2020), divided in different regimes of bolometric luminosity, is shown in the right panel of Fig. 5.…”
Section: X-ray Weaknessmentioning
confidence: 93%

X-ray spectroscopic survey of highly-accreting AGN

Laurenti,
Piconcelli,
Zappacosta
et al. 2021
Preprint
Self Cite